1986
DOI: 10.1111/j.1749-7345.1986.tb00551.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Five Stocking Densities on Growth and Yield of Red Swamp Crawfish Procambarus clarkii

Abstract: A 34‐day study was conducted to estimate the effect of stocking density on growth, biomass, and yield of harvestable animals in red swamp crawfish, Procambarus clarkii (Girard). Juvenile crawfish were stocked at l, 2, 4, 8, and 16 crawfish per m2 into plastic‐lined metal pools planted with rice (Oryza sativa) with three replicate pools at each density. Crawfish averaged 35 ± 1.5 mm (SE) total length at the time of stocking.Growth in total length and weight was significantly affected by density (P < 0.01), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 0 publications
2
36
1
Order By: Relevance
“…The effect of stocking density on crustacean production has been extensively studied in the context of commercial aquaculture. Most of these studies have found the growth rate to be inversely related to stocking density, even when food was not a limiting factor (Lutz & Wolters 1986, D'Abramo et al1989, NaranjoPáramo et al 2004. The 3 locations we surveyed exhibited different population densities.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of stocking density on crustacean production has been extensively studied in the context of commercial aquaculture. Most of these studies have found the growth rate to be inversely related to stocking density, even when food was not a limiting factor (Lutz & Wolters 1986, D'Abramo et al1989, NaranjoPáramo et al 2004. The 3 locations we surveyed exhibited different population densities.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have studied the effect of stocking density under rearing conditions in Australian species (Geddes, Smallridge, & Clark 1993;Morrissy, Bird, & Cassels 1995;Whisson 1995), the red crayfish Procambarus clarkii (Lutz & Wolters 1986;McClain 1995) and the white crayfish Pascifastacus leniusculus (Westman 1973;Mason 1979). However, there have not yet been any density and growth rate studies for Cambarellus montezumae.…”
Section: Introductionmentioning
confidence: 99%
“…Data were expressed as mean ± SD and analyzed using One-way ANOVA followed by Duncan's multiple-range test (Lutz et al, 2007). A value of p<0.05 was considered as statistically significant.…”
Section: Discussionmentioning
confidence: 99%